The Cost Efficiency and Profitability for Commercial Banks: An Empirical Analysis from China. - Lin, Yan (2018)
By selecting sample data from 167 Chinese commercial banks between 2013 and 2017, the study first uses SFA to estimate the cost efficiency of these banks and finds that the mean cost efficiency value of banks remains at a high level during the research years. Moreover, the average efficiency value is accompanied by an upward trend with fluctuations, which is in consistent with some previous studies. After that, three types of variables are utilised in the GMM model, including bank-specific, industry-specific and macroeconomic factors, to estimate the determinants of Chinese commercial bank profitability. According to the empirical results, bank size, credit risk and capitalisation are positively associated with bank performance, while the coefficients of z-score and branch networks give negative signs. Furthermore, there are some mixed findings of liquidity, non-interest activities and cost efficiency. Additionally, Chinese commercial banks are significantly affected by external factors. High concentration ratio leads to low profitability, while GDP growth and unemployment rate have a positive effect on bank performance.